2018
DOI: 10.23880/oajds-16000183
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Mandibular Third Molar Impaction and Relationship to the Inferior Alveolar Canal: Retrospective Cone Beam Computed Tomography Analysis in a Group of Sri Lankan Patients

Abstract: Cone beam computed tomography (CBCT) provides a precise three dimensional analysis of vicinity of Impacted Mandibular third molar (IMTM) which helps in surgical decision making.Objective: Objective of this study was to analyze the pattern of IMTM and the relationship of inferior alveolar canal to the tooth in 68 patients presented in year 2014 University Dental Hospital, Sri Lanka. Methods:The study sample included 112 IMTM teeth in 68 patients (54.5 % females, 45.5 % males) with average age of 28 years. Preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
3
0
1
Order By: Relevance
“…Level B impaction was the most common level of impaction identified in the present study, a finding that is consistent with several previous studies [ 2 , 17 , 18 , 20 , 21 ]. However, other previous studies have found a higher level of impaction, where level A was the most common level [ 3 , 4 , 6 , 14 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Level B impaction was the most common level of impaction identified in the present study, a finding that is consistent with several previous studies [ 2 , 17 , 18 , 20 , 21 ]. However, other previous studies have found a higher level of impaction, where level A was the most common level [ 3 , 4 , 6 , 14 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…This last method provides more accurate results and allows the methodology of the study to be reproduced. In accordance with our findings, many previous studies have also shown that mesioangular impaction is the most common type of impaction [ 2 4 , 7 , 8 , 14 , 17 21 , 23 ]. On the other hand, some other previous reports demonstrated that the vertical type of MTM impaction is the predominant impaction type [ 6 , 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations